Decision Support System for Household Labor Services Selection “Best Helper” Using AHP and TOPSIS Methods - Pirnanda, I Kadek Aditya; Pradnyana, I Made Ardwi; Wirawan, I Made Agus (Universitas Negeri Semarang, 2019)
Selection of household labor services was an important aspect in families who have a lot of activity. The existence of helpful household labour services would avoid the occurrence of problems that should be caused. Types of household labour services which were often used were maids, baby sitters, elderly nurses, gardeners, and drivers. The main problem arose in the difficulty of service seekers in choosing the desired service and how to minimize the time spent. To overcome this, a decision support system was used using the Analytical Hierarchy Process (AHP) method which was used to find the criteria for each alternative weight, and ranking calculations using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. This research was implemented using PHP language with CodeIgniter framework. The result shows that the usability test obtains the average value with the system usability scale (SUS) method of 71.09%. It shows that the level of system usability is classified as good and can be accepted and used easily by the users. Meanwhile, the result of the user response test shows a percentage of 87.5%, so it can be concluded that the system belongs to good category and feasible to use.